PPE Model for Misconception Remedial of Science for Junior High School Students - Rumiyati Rumiyati; Indrawati Indrawati; Sutarto Sutarto; Iwan Wicaksono (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
This article is a result of developmental research of PPE (Peer, Tutoring, Presentation, and Evaluation) model for remedy several science misconceptions: work, kinetic energy, the potential energy of junior high school students. The research aims to describe the science misconceptions of students and the effectiveness PPE model to remedy students’ misconceptions. The research was conducted by 31 students of SMP 1 Kencong, Jember Regency, who had misconceptions of those concepts. Technique for collecting data was test and interview. The data collection were analysed qualitatively descriptive. Findings of the research were: Most of the students had three kinds of misconceptions, they said that if a body has a force, it also has work; if velocity of body increased three times, so the kinetic energy increased three times; in freely falling bodies, when an object approaches the ground, it has null kinetic energy and high potential energy. The effectiveness of the PPE model to remedy those students’ misconceptions can be seen from positive students’ responses to the implementation of the model to remedy their misconceptions and the average of the number of students’ misconceptions decrease from 100% to 15,4%. The study can be concluded that the PPE model effective for remedy students’ misconceptions of work, kinetic energy, and potential energy concepts.